2014
DOI: 10.2337/dc13-1973
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Moderate-to-Vigorous Intensity Physical Activity on Overnight and Next-Day Hypoglycemia in Active Adolescents With Type 1 Diabetes

Abstract: OBJECTIVEPhysical activity (PA) provides many benefits to adolescents with type 1 diabetes; however, these individuals tend to have lower fitness and PA levels than their disease-free counterparts. The purpose of this study was to examine the acute temporal associations between moderate-to-vigorous intensity PA (MVPA) and hypoglycemia (continuous glucose monitor [CGM] reading ≤70 mg/dL).RESEARCH DESIGN AND METHODSNineteen participants (53% females) 14–20 years old with type 1 diabetes were recruited. Participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(55 citation statements)
references
References 21 publications
2
53
0
Order By: Relevance
“…However, three studies found no association between PA and glycemic control (Kalweit, Briers, & Olorunju, ; Keel et al., ; Mosso et al., ). For blood glucose regulation, in the case‐control study with 200 adolescents who were instructed to cross the maximum distance in meters following the 6‐min walk test, a positive effect of PA on blood glucose without increasing the risk for hypoglycemia was noted (Jegdic et al., ; Metcalf et al., ). Three cross‐sectional studies observed a significant positive association between reported PA and HDLs and a significant negative association with LDLs (Heyman et al., ; Mohammed et al., ; Parthasarathy et al., ).…”
Section: Resultsmentioning
confidence: 99%
“…However, three studies found no association between PA and glycemic control (Kalweit, Briers, & Olorunju, ; Keel et al., ; Mosso et al., ). For blood glucose regulation, in the case‐control study with 200 adolescents who were instructed to cross the maximum distance in meters following the 6‐min walk test, a positive effect of PA on blood glucose without increasing the risk for hypoglycemia was noted (Jegdic et al., ; Metcalf et al., ). Three cross‐sectional studies observed a significant positive association between reported PA and HDLs and a significant negative association with LDLs (Heyman et al., ; Mohammed et al., ; Parthasarathy et al., ).…”
Section: Resultsmentioning
confidence: 99%
“…The risk of overnight and next-day hypoglycemia is particularly problematic if moderate to vigorous exercise is undertaken in the afternoon or early evening. 25,26 Late-onset hypoglycemia following exercise increases with the duration of exercise and the fitness of the exercisers, and activities lasting 90 to 120 minutes double the risk of hypoglycemia in adolescents and young adults. 26 …”
Section: Exercise Variablesmentioning
confidence: 99%
“…An appropriately powered randomized control trial comparing control achieved in subjects managed with activity monitor and semi‐automated basal adjustment vs standard CGM‐enabled pump therapy is needed to confirm whether glucose control is improved. Sensor‐enabled insulin pumps with low glucose suspend, or closed‐loop systems, may eventually eliminate the need to reduce nighttime basal rates following high activity days; however, it may not be feasible or advisable for every patient to be on these systems all the time. Lastly, integration of activity data into closed‐loop algorithms, which could feasibly be done if an accelerometer were integrated into the insulin pump, may also help optimize glycemic control.…”
Section: Discussionmentioning
confidence: 99%
“…Despite these advances, many patients continue to use standard insulin pumps with no automation, and the opportunity to optimize how these pumps are configured remains. This is particularly true in relation to varying insulin requirements associated with physical activity, as exercise is known to be associated with higher risk of overnight and even next‐day‐hypoglycemia in children and adolescents with T1DM . Although the DirectNet Study Group showed reductions in hypoglycemia with basal rate suspension, the suspensions were only initiated in response to low glucose or impending low glucose .…”
Section: Introductionmentioning
confidence: 99%